Crop and soil suitability analysis using multi-criteria decision making in drought-prone semi-arid tropics in India - JAIN, RAJNI; CHAND, PREM; RAO, SULAKSHNA C.; AGARWAL, PRIYANKA (Journal of Soil and Water Conservation, 2020)
Land suitability analysis for crops is a pre-requisite for optimum utilization of the available resources and sustainable agricultural production. The present study proposes a framework for crop suitability estimation using 13 agricultural crops in Bundelkhand region using attributes like soil, climate, topography, socio-economic factors and infrastructural facilities. In proposed framework, all attributes and parameters were standardised and matched with the thresholds applicable for each crop. The cropwise required thresholds levels for each suitability category for all attributes and parameters were also developed. Analytical Hierarchy Process has been used to assign weights for each criteria, combining them and reaching an overall suitability for each crop in the region. The results revealed that most of the existing crops are either moderately or marginally suitable for cultivation. Further analysis highlighted that farmers are not cultivating the crops based on suitability of biophysical and irrigation parameters (indicator of sustainability) but based on suitability of socio-economic parameters. If this trend continues, ecosystem will suffer in longer run. Thus, there is a need for creating awareness among farming community and also revising price policy so as to improve socio-economic suitability of crops in favour of biophysically suitable crops.